Petrology of rhyolitic and mixed magma ejecta from the 1875 eruption of Askja, Iceland - Sigurdsson, H.; Sparks, R. S.J. (Journal of Petrology, 1981)
Volcanic activity in Askja central volcano and its fissure swarm in 1875 occurred in response to a crustal rifting episode in Iceland, resulting in up to 70 km lateral flow of magma within the crust, caldera collapse and a plinian eruption of acid magma (0·2 km3 dense-rock equivalent). Petrologic studies of the predominantly rhyolitic and crystal-poor ejecta reveal that a complex array of other liquid compositions was also present, including icelandite (0.75 per cent) and basalt (1.9 per cent), as well as leucocratic xenoliths of trondhjemite type. Mineral geothermometers indicate that the rhyolite evolved at 990 to 1010 °C and 0·5 Kb PH2O, the icelandite at 1005 to 1020 °C and at fo2 10-10 atm. and the basalt at 1140 to 1170 °C.A petrologic model of Askja in 1875 consists of a density-stratified magma chamber with a rhyolitic upper part and a lower part of ferrobasalt, with an intervening layer of icelandite. The model calculations show that the icelandite can be derived from ferrobasalt by 50 per cent fractional crystallization, but one-stage fractional crystallization models cannot account for generation of the acid magma. Simple partial or complete fusion of the field-associated trondhjemite xenoliths cannot produce the acid magma. Instead, a more complex fusion, hybridization and fractional crystallization model is presented, which is consistent with the available petrologic evidence. This model involves large-scale fusion of pre-existing trondhjemite intrusions or reactivation of previously consolidated roof-rock in the magma chamber followed by hybridization of the acid magma with 7 to 14 per cent basaltic magma. Finally, 10 to 11 per cent fractional crystallization of the dacite hybrid is required to produce the observed compositional range within the rhyolite ejecta. The 1875 explosive eruption was caused by the ascent of tholeiitic basalt magma from depth during crustal rifting. Influx of new basalt magma in 1874-75 triggered convective mixing and hybridization in the compositionally zoned magma ...